Robust Immune Response Induced by Schistosoma mansoni TSP-2 Antigen Coupled to Bacterial Outer Membrane Vesicles - Barbosa MMF (Dove Medical Press, 2021)
Mayra M F Barbosa,1,2 Alex I Kanno,1 Giovana C Barazzone,1 Dunia Rodriguez,1 Violeta Pancakova,1,3 Monalisa Trentini,1 Eliana L Faquim-Mauro,4 Amanda P Freitas,4 Mariana I Khouri,5 Jessica Lobo-Silva,5 Viviane M Goncalves,1 Rocilda P F Schenkman,1 Martha M Tanizaki,1 Diana Boraschi,6– 8 Richard Malley,9 Leonardo P Farias,5 Luciana C C Leite1 1Laboratório de Desenvolvimento de Vacinas, Instituto Butantan, São Paulo, Brazil; 2Programa de Pós-Graduação Interunidades em Biotecnologia, Universidade de São Paulo, São Paulo, Brazil; 3Université Claude Bernard Lyon 1 (UCBL1), Villeurbanne, 69100, France; 4Laboratório de Imunopatologia, Instituto Butantan, São Paulo, Brazil; 5Laboratório de Biomarcadores e Inflamação, Instituto Gonçalo Moniz, Fundação Oswaldo Cruz, Salvador, Brazil; 6Istituto di Biochimica e Biologia Cellulare, Consiglio Nazionale delle Ricerche, Napoli, Italy; 7Stazione Zoologica Anton Dohrn, Napoli, Italy; 8Shenzhen Institute of Advanced Technologies (SIAT), Chinese Academy of Sciences (CAS), Shenzhen, China Division of Infectious Diseases, Boston Children’s Hospital, Boston, MA, USA; 9Division of Infectious Diseases, Boston Children’s Hospital, Boston, MA, USACorrespondence: Luciana C C LeiteLaboratório de Desenvolvimento de Vacinas, Instituto Butantan, Av. Vital Brasil, São Paulo, 1500, SP, BrazilTel +55-11-2627-9816Email luciana.leite@butantan.gov.brPurpose: The use of adjuvants can significantly strengthen a vaccine’s efficacy. We sought to explore the immunization efficacy of bacterial outer membrane vesicles (OMVs) displaying the Schistosoma mansoni antigen, SmTSP-2, through a biotin-rhizavidin coupling approach. The rationale is to exploit the nanoparticulate structure and the adjuvant properties of OMVs to induce a robust antigen-specific immune response, in light of developing new vaccines against S. mansoni.Materials and Methods: OMVs were obtained from Neisseria lactamica and conjugated with biotin. The recombinant SmTSP-2 in fusion with the biotin-binding protein rhizavidin (rRzvSmTSP-2) was produced in E. coli and coupled to biotinylated OMVs to generate an OMV complex displaying SmTSP-2 on the membrane surface (OMV:rSmTSP-2). Transmission electron microscopy (TEM) and dynamic light scattering analysis were used to determine particle charge and size. The immunogenicity of the vaccine complex was evaluated in C57BL/6 mice.Results: The rRzvSmTSP-2 protein was successfully coupled to biotinylated OMVs and purified by size-exclusion chromatography. The OMV:rSmTSP-2 nanoparticles showed an average size of 200 nm, with zeta potential around – 28 mV. Mouse Bone Marrow Dendritic Cells were activated by the nanoparticles as determined by increased expression of the co-stimulatory molecules CD40 and CD86, and the proinflammatory cytokines (TNF-α, IL-6 and IL-12) or IL-10. Splenocytes of mice immunized with OMV:rSmTSP-2 nanoparticles reacted to an in vitro challenge with SmTSP-2 with an increased production of IL-6, IL-10 and IL-17 and displayed a higher number of CD4+ and CD8+ T lymphocytes expressing IFN-γ, IL-4 and IL-2, compared to mice immunized with the antigen alone. Immunization of mice with OMV:rSmTSP-2 induced a 100-fold increase in specific anti-SmTSP-2 IgG antibody titers, as compared to the group receiving the recombinant rSmTSP-2 protein alone or even co-administered with unconjugated OMV.Conclusion: Our results demonstrate that the SmTSP-2 antigen coupled with OMVs is highly immunogenic in mice, supporting the potential effectiveness of this platform for improved antigen delivery in novel vaccine strategies.Keywords: Schistosoma mansoni, vaccine, TSP-2 antigen, outer membrane vesicles, OMV, biotin-avidin coupling, nanoparticle